Speechmaking and the Selectorate: Persuasion in Nonpreferential Electoral Systems - Fernandes, Jorge (2019)
This article examines the extent to which legislators use legislative debates to engage in localism activities to cater to the interests of their selectorate in nonpreferential electoral systems. We define localism activities as the delivery of tangible and intangible benefits to a geographically confined constituency that is instrumental to legislators’ re-selection. Our primary argument is that legislators whose selectorate operates at the local level make more speeches with parochial references. Results show strong support for this assertion. Furthermore, we find that high district magnitude leads to higher levels of localism. We use a mixed-methods research design, combining an original data set of 60,000 debates in Portugal with qualitative evidence from elite interviews. We make a methodological innovation in the field of representation and legislative studies by using a Named Entity Recognition tool to analyze the debates.